Use of a complex mixture of hyphomycete Lecanicillium lecanii and Bacillus thuringiensis to protect greenhouse crops from sucking pests - Shcherbakova , T. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2025)
Goal. To determine the biological effectiveness of working suspensions of hyphomycete Lecanicillium lecanii, bacterium Bacillus thuringiensis var. thuringiensis and their mixture in regulating the number of melon aphids and common spider mites on cucumber culture in closed ground conditions.Methods. Laboratory and in the experimental greenhouse block. Objects of research: 1) entomopathogenic fungus Lecanicillium lecanii R. Zare & W. Gams (2001), strain CNMN-FE-03, isolated from the natural population of greenhouse whitefly with subsequent selection by passage through the test insect. Three passages through melon aphids and three passages through common spider mites were performed; 2) entomopathogenic bacterium Bacillus thuringiensis var. thuringiensis (Bt) was isolated from a dead larva of the Colorado potato beetle. Target objects are melon aphid Aphis gossypii Glov. and common spider mite Tetranychus urticae Koch.Results. The technical efficiency of the aqueous suspension of hyphomycete L. lecanii at a concentration of 3.5% against melon aphids was 89.9%, against spider mites — 92.7%. The bacterial suspension of B. thuringiensis at a concentration of 5.0% reduced the number of aphids by 89.1%, the number of spider mites — by 91.1%. The technical efficiency of the mixture of suspensions of the fungus L. lecanii at a concentration of 3.5% and the bacterial suspension of B. thuringiensis at a concentration of 5.0% against melon aphids was 91.7%, against spider mites — 93.8%. Conclusions. As a result of the studies, it was noted that the combined use of two biological insecticidal plant protection products based on the fungus L. lecanii (contact action) and the bacterium B. thuringiensis var. thuringiensis (intestinal action) increases the percentage of common spider mites and melon aphids in closed ground conditions by 1.1—2.7% compared to their use separately.